2017
DOI: 10.1165/rcmb.2016-0174oc
|View full text |Cite
|
Sign up to set email alerts
|

The Superiority of IFN-λ as a Therapeutic Candidate to Control Acute Influenza Viral Lung Infection

Abstract: Here, we studied the IFN-regulated innate immune response against influenza A virus (IAV) infection in the mouse lung and the therapeutic effect of IFN-λ2/3 in acute IAV lung infection. For viral infections, IAV (WS/33, H1N1, PR8 H1N1, H5N1) were inoculated into wild-type mice by intranasal delivery, and IAV mRNA level and viral titer were measured. To compare the antiviral effect of IFNs in vivo in the lung, neutralizing antibodies and recombinant IFNs were used. After intranasal inoculation of IAV into mice,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 43 publications
0
67
0
Order By: Relevance
“…Our inability to reduce MERS-CoV titer or improve outcomes with IFN as described above may be due to inherent differences in the animal ARTICLE models, delivery route, differences in IFN subtype and/or active viral antagonism of innate immunity. Since recent studies have demonstrated type III IFN to be most effective in ameliorating influenza pathogenesis in mice, comparative studies investigating the potency of different IFN subtypes should be pursued with MERS-CoV [43][44][45] . Acute lung injury (ALI) in humans is well defined by a set of clinical parameters (i.e., acute onset, diffuse bilateral infiltrates on X-ray, ratio of partial pressure of arterial oxygen to inspired oxygen < 300, no evidence of elevated pulmonary arterial pressure, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Our inability to reduce MERS-CoV titer or improve outcomes with IFN as described above may be due to inherent differences in the animal ARTICLE models, delivery route, differences in IFN subtype and/or active viral antagonism of innate immunity. Since recent studies have demonstrated type III IFN to be most effective in ameliorating influenza pathogenesis in mice, comparative studies investigating the potency of different IFN subtypes should be pursued with MERS-CoV [43][44][45] . Acute lung injury (ALI) in humans is well defined by a set of clinical parameters (i.e., acute onset, diffuse bilateral infiltrates on X-ray, ratio of partial pressure of arterial oxygen to inspired oxygen < 300, no evidence of elevated pulmonary arterial pressure, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Type I IFNs, including interferon-␣ (IFN␣) and interferon-␤ (IFN␤), are important for limiting viral replication and spread. Type III interferons, known as interferon-(IFN), are also produced early after viral recognition and have been shown to be important in viral infection (19). IP-10 production is also controlled by IFN signaling.…”
Section: L507 Cigarette Smoke Disrupts Tlr3 Cleavagementioning
confidence: 99%
“…When IL-27 was administered early in infection, it resulted in impaired viral clearance and worsened disease; however, when administered late in infection, there was decreased pathology, increased survival, and no impact on viral clearance. Other examples of factors that modulate both tolerance and resistance in this kind of reciprocal fashion are TGF-β, IL-10, and interferons, particularly type III (72,(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143).…”
Section: Modulating Tolerance Mechanisms To Infections Can Impact Dismentioning
confidence: 99%